Impact of insomnia upon inflammatory digestive diseases and biomarkers: a two-sample mendelian randomization research on Europeans - Lei Dai; Yunyan Ye; Joseph Mugaanyi; Caide Lu; Changjiang Lu (BMC Gastroenterology, 2024)
Abstract Background A number of observational studies indicate that insomnia is linked to inflammatory digestive diseases (IDDs). However, the definite relationship between insomnia and IDDs remains unclear. Methods We obtained the publicly available data from genome-wide association studies (GWAS) to conduct two-sample Mendelian randomization (MR) for association assessment. Five MR analysis methods were used to calculate the odds ratio (OR) and effect estimate, and the heterogeneity and pleiotropy tests were performed to evaluate the robustness of the variable instruments (IVs). Results One exposure and twenty outcome datasets based on European populations were included in this study. Using the inverse variance weighted method, we found insomnia was closely correlated with esophageal ulcer (OR = 1.011, 95%CI = 1.004–1.017, p = 0.001) and abdominal pain (effect estimate = 1.016, 95%CI = 1.005–1.026, p = 0.003). Suggestive evidence of a positively association was observed between insomnia and duodenal ulcer (OR = 1.006, 95%CI = 1.002–1.011, p = 0.009), gastric ulcer (OR = 1.008, 95%CI = 1.001–1.014, p = 0.013), rectal polyp (OR = 1.005, 95%CI = 1.000-1.010, p = 0.034), haemorrhoidal disease (OR = 1.242, 95%CI = 1.004–1.535, p = 0.045) and monocyte percentage (effect estimate = 1.151, 95%CI = 1.028–1.288, p = 0.014). No correlations were observed among other IDDs, phenotypes and biomarkers. Conclusions Our MR study assessed the relationship between insomnia and IDDs/phenotypes/biomarkers in depth and revealed potential associations between insomnia and ulcers of the esophagus and abdominal pain.